A double-blind randomized clinical trial on the suggestive effect of anxiety management questionnaires in dental emergencies - Benz, Carla Irene; Wolanski, Celina; Piefke, Martina; Campus, Guglielmo; Piwowarczyk, Andree; Wolf, Thomas Gerhard (Frontiers in Psychology, 2024)
Objective Dental anxiety is widespread among both children and adults. To diagnose dental anxiety, standardized anxiety questionnaires are recommended. Based on the suggestive nature of the questionnaires, the study aimed to find out whether asking respondents about personal coping strategies before dental treatment influences their anxiety. Methods This prospective, double-blind, randomized controlled clinical trial included a total of 158 patients of a university dental clinic on emergency service. The intervention group (n = 82) received the Coping with Anxiety Questionnaire (CAQ) and the control group (n = 76) the Hierarchical Anxiety Questionnaire (HAF). State anxiety scores were assessed by using the State–Trait Anxiety Inventory (STAI) before and after the completion of each questionnaire. Results Anxiety decreased in the intervention group (CAQ) (p < 0.001) and increased in the control group (HAF) (p < 0.001). Conclusion Within the limitations of the current study, a diagnostic tool of a standardized questionnaire for the assessment to assess personal coping strategies decreased state anxiety in comparison to a questionnaire assessing anxiety. Clinical trial registration https://www.drks.de, German Trials Register (DRKS00032450).